STRATEGI PENGEMBANGAN AGRIBISNIS MELALUI AGRIBUSINNESS DEVELOPMENT CENTER DALAM MEMBANGUN KEMITRAAN AGRIBISNIS (Studi pada Pengembangan Sentra Usaha Peternakan Sapi Kecamatan Tawangsari, Kabupaten Sukoharjo) - Sugiharti Mulya Handayani; Raden Kunto Adi; Setyowati Setyowati; Susi Wuri Ani (Caraka Tani: Journal of Sustainable Agriculture, 2012)
This research aimed to identify needs and problems the small and medium enterprises of agribusiness, to formulate the internal and external factors in to strengthness, weakness, opportunities and treatness in development of agribusiness, to formulate alternative strategies in development of agribusiness with agribusiness development center in developing of agribusiness partnership, to formulate the priority strategies in development of agribusiness with agribusiness development center in developing of agribusiness partnership, and to formulate the value chain in development of agribusiness with agribusiness development center in developing of agribusiness partnership at Sukoharjo Regency. Te basic method used in this research is descriptive analytic method with survey techniques and focus group discussion. The method to determine the location of the research done by purposive, namely Sukoharjo Regency. Sampling method to determine the factors internal and external done snowball, while the method of determining the weight and attractiveness Score (AS) performed intentionally (purposively). Data type applied in this research is primary data and secondary data. Data analysis method applied were SWOT analysis, SWOT matrix, QSP matrix, and value chain analysis. The results of SWOT analysis to show internal factors that the strengths in developing agribusiness of cattle cow were a large of many and expand of cattle breeder in Sukoharjo Regency, quality of cow were good and continuity of production, a large of many potency of nature resources, institution of cluster were strength. The weakness were production factors are limited, especially of cattle food, a low of capacity of human resources in to access for breeding and technology, health of cow, access of market and information of price, a lack of marketing, a low of optimally in management of cattle, management of cattle still traditionally, and hereditary, and so a lack of capital capacity. The external factors that the opportunities were simplify of capital access at banking, institution of micro finance, credits with light of interest, a large of foods cattle from small and medium enterprises central else, a demand of met cow and product of meat cow processing, a development policy of small and medium enterprises from province and state government, technology processing of process remainder of cattle, easier of development quality of meat and breeding. The treathness were a limited of superior of seed, a limited of production factors, especially of food cattle, a association or cooperation of cattle breeder was not yet, a import policy of meat cow, a policy programme of small and medium enterprises development was not well coordinated, a finance capacity of regional government for development of small and medium enterprises was limited, a technology processing of remainder process of cattle was limited, a infection of antrax disease from other location and other disease that lack of prediction, a price competition of cow with other location from Sukoharjo Regency that usually of lower price. The results of SWOT Matrix and QSP to show priority strategies can be applied in development agribusiness of cattle cow were developing and to defend of quality and continuity production to endure in the markets, with development of production capacity and technology, and so cluster institution with supported by coordinatively stakeholders, so that strengthening of bargaining position of cattle breeder, to develop capacity of human resources of cattle breeder for developing access in to production factors and technology, to develop business management, to defend and expanding markets access, with coordination and cooperation with stakeholders as like non regional government institution, and to defend of production quality and continuity by partnership with other central of small and medium enterprises in performing of production factors and distribution networking.